The piety of learning: Islamic studies in honor of Stefan Reichmuth - Kemper, Michael; Elger, Ralf; Reichmuth, Stefan (Islamic history and civilization, 2017)
The Piety of learning / Michael Kemper and Ralf Elger -- ʻIlm and adab revisited: knowledge transmission and character formation in Islamic Africa / Rudiger Seesemann -- From the intellectual powerhouse of Ilorin (Nigeria): elegy in the work of Adam ʻAbdallah al-Iluri (1917-1992) / Amidu Olalekan Sanni, assisted by Yunus Alade Salman -- The Khadimis of Konya: the rise of a scholarly family from the Ottoman periphery / Yasar Sarikaya --Moral education in Central Asia, 19th-21st centuries: the foundations for Sufi, Jadid, Soviet, National, and Islamist ethics / Anke von Kugelgen -- The small world of Aḥmad al-Ḥawi (1761-1825), an Egyptian Khalwati Shaykh / Catherine Mayeur-Jaouen -- Abu l-Huda al-Sayyadi and ḥadith / Thomas Eich -- Sayfallah-Qaḍi Bashlarov: Sufi networks between the North Caucasus and the Volga-Urals / Shamil Shikhaliev and Michael Kemper -- Against Leviathan: on the ethics of Islamic poetry in Soviet Russia / Alfrid K. Bustanov -- Blessing and curse in the "Promised Land": Jonas Korte's travels in the Ottoman Empire, 1737-1739 / Ralf Elger -- Omer Pasha Latas and the Ottoman reform policy in Bosnia and Herzegovina (1850-1851) / Markus Koller -- The pilgrim's tale as a means of self-rromotion: Muḥammad Rashid Riḍa's journey to the Ḥijaz (1916) / Rainer Brunner -- Scholarly exchange and trade: Muḥammad Ḥusayn Naʼif and his letters to Christiaan Snouck Hurgronje / Ulrike Freitag -- Rescuing the Tatar Muslim heritage in the Soviet Union: the Expedition diaries of Mirkasym A. Usmanov / Diliara M. Usmanova -- Islamic theological studies in Germany: a discipline in the making / Bekim Agai and Armina Omerika -- Stefan Reichmuth's wanderings in Arabicized and Islamized Yorubaland / Razaq 'Deremi Abubakre